The Potential of Edu-Ecotourism 'Floradventure' in Djuanda Forest Park, Bandung - Fauziah, Abidah; Surakusumah, Wahyu; Polando, Chersy Tiffany; Fadhilah, Fathan; Abthal, Ok M. (-, 2024)
Ir. H. Djuanda Forest Park (Tahura) is a protected area of 526.98 hectares that functions as a protected forest and tourist attraction. With 85% local flora and 15% from other bioregions, Tahura provides research, education, and recreation facilities. The area is made up of secondary natural forest and plantation forest, serving as a natural laboratory with vegetation from 40 families and 112 species, including both native and exotic plants. This research aims to develop the educational tourism package "Floradventure" to help tourists recognize the flora of Tahura Djuanda. The study was conducted in March 2024 using qualitative descriptive methods, feasibility study analysis, and SWOT analysis. The results show that the 'Floradventure' ecotourism site in Tahura has advantages in terms of accessibility, public facilities, and potential collaboration for additional facilities. Careful planning and evaluation are necessary for the success and sustainability of this educational tourism package.